2008
DOI: 10.1158/0008-5472.can-08-0951
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Adenomatous Polyposis Coli Gene by the miR-135 Family in Colorectal Cancer

Abstract: Inactivation of the adenomatous polyposis coli (APC) gene is a major initiating event in colorectal tumorigenesis. Most of the mutations in APC generate premature stop codons leading to truncated proteins that have lost B-catenin binding sites. APC-free B-catenin stimulates the Wnt signaling pathway, leading to active transcription of target genes. In the current study, we describe a novel mechanism for APC regulation. We show that miR-135a&b target the 3 ¶ untranslated region of APC, suppress its expression, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
380
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(411 citation statements)
references
References 40 publications
23
380
0
1
Order By: Relevance
“…In summary, our results point to the notion that blockage of constitutive Wnt signaling in CRC cells lead to upregulation of several growth-suppressive miRNAs, thus paralleling the functional response observed at the mRNA level where numerous negative growth regulators (for example, FOXO3A, DAPK2, HATH1 and CDKN1A/p21) are known to be induced under similar conditions in CRC cells (van de Wetering et al, 2002;Tsuchiya et al, 2007;Dehner et al, 2008;Li et al, 2009). Remarkably, recent studies indicate that miRNAs also shape the potency of the Wnt cascade itself by repressing key components (Nagel et al, 2008;Saydam et al, 2009). We therefore believe that our results, in aggregate with those of others, collectively support the rationale that a full appreciation of Wnt signaling should involve the contribution of non-coding RNAs such as miRNAs.…”
Section: Discussionsupporting
confidence: 79%
“…In summary, our results point to the notion that blockage of constitutive Wnt signaling in CRC cells lead to upregulation of several growth-suppressive miRNAs, thus paralleling the functional response observed at the mRNA level where numerous negative growth regulators (for example, FOXO3A, DAPK2, HATH1 and CDKN1A/p21) are known to be induced under similar conditions in CRC cells (van de Wetering et al, 2002;Tsuchiya et al, 2007;Dehner et al, 2008;Li et al, 2009). Remarkably, recent studies indicate that miRNAs also shape the potency of the Wnt cascade itself by repressing key components (Nagel et al, 2008;Saydam et al, 2009). We therefore believe that our results, in aggregate with those of others, collectively support the rationale that a full appreciation of Wnt signaling should involve the contribution of non-coding RNAs such as miRNAs.…”
Section: Discussionsupporting
confidence: 79%
“…All analyzed miRNAs were down-regulated to a certain degree by butyrate or TSA after 24-or 48-h incubation, respectively. Studies revealed that miR-135a and miR-135b exhibit an oncogenic potential, by inhibiting expression of APCs (Nagel et al 2008). Recently, Valeri et al (2014) demonstrated that miR-135b promotes cancer progression by acting as a downstream effector of oncogenic pathways in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, miR-135a seems to be an onco-like miRNA by targeting APC (Nagel et al, 2008). But in classic Hodgkin's lymphoma, this miRNA can induce apoptosis of L-428 cells by targeting JAK2 (Navarro et al, 2009).…”
Section: Discussionmentioning
confidence: 99%